The State of Renewable Energy in Kenya with a Focus on the Future of Hydropower - Chemengich, S. J.; Masara, D. O. (Africa Environmental Review Journal, 2022)
The rise in global energy demand and the need to reduce greenhouse gas emissions have necessitated the transition to renewables. Many previously unelectrified countries in Sub-Saharan Africa have joined the race to provide their people with clean, reliable, and affordable energy. Kenya is amongst the countries that are leading in powering their energy demands from renewables with over 80% of its energy being green. As economic development advances toward fulfilling Vision 2030 targets, the country's electricity consumption, as well as the end-use of energy, has increased significantly during the last decade. To achieve universal access to electricity and a complete transition to renewables, not only must energy sources be diversified, but they must also be fully exploited. This study aims to highlight Kenya's current energy situation, with a focus on how hydropower could be fully utilized to meet the country's long-term energy demands sustainably.